2023
DOI: 10.22541/essoar.168748473.37219221/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating Ecosystem-Scale Responses to Compost Amendments in a Grazed Grassland

Abstract: Compost amendments to rangelands is a proposed nature-based climate solution to increase plant productivity and soil carbon sequestration. However, it has not been evaluated using semi-continuous ecosystem-scale measurements. Here we present the first study to utilize eddy covariance and footprint partitioning to monitor carbon exchange in a grassland with and without compost amendment, monitoring for one year before and one year after treatment. Compost amendments to an annual California grassland were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…In addition, the significant increase in aboveground biomass three years after the compost application indicate the persistence of favorable plant growing conditions, such as increased N in the soil. These results are in accordance with Fenster et al (2023), who found that the benefits of compost treatments on the ecosystem C balance of grasslands one year after application were manifested as extended growing season, and thus potentially higher plant productivity, rather than as an increase in net soil C. This also stresses the importance of including vegetation dynamics when assessing the effectiveness of C management.…”
Section: Landscape Spatial Variabilitysupporting
confidence: 90%
“…In addition, the significant increase in aboveground biomass three years after the compost application indicate the persistence of favorable plant growing conditions, such as increased N in the soil. These results are in accordance with Fenster et al (2023), who found that the benefits of compost treatments on the ecosystem C balance of grasslands one year after application were manifested as extended growing season, and thus potentially higher plant productivity, rather than as an increase in net soil C. This also stresses the importance of including vegetation dynamics when assessing the effectiveness of C management.…”
Section: Landscape Spatial Variabilitysupporting
confidence: 90%